2022
DOI: 10.3389/fsufs.2022.938128
|View full text |Cite
|
Sign up to set email alerts
|

Foliar Silicon Spray to Strawberry Plants During Summer Cutting Propagation Enhances Resistance of Transplants to High Temperature Stresses

Abstract: Silicon (Si) has been reported to benefit plant growth and stress resistance. This work aimed to find out an optimal method of Si application to enhance the resistance of strawberry (Fragaria × ananassa Duch.) transplants to high temperatures, commonly experienced in the summer when strawberries are propagated for greenhouse production in Korea. Plants of strawberry “Sulhyang”, “Maehyang”, and “Kuemsil” were subjected to one of five treatments before the cutting propagation: no treatment (control), substrate d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 94 publications
0
3
0
Order By: Relevance
“…The following studies also reported that Si treatments signi cantly improved vegetative growth in strawberry plants [46,48,49] and other plants [50,51]. The differential response of the potassium silicate treatment in strawberry plants improved the 'plant's physiological traits, such as leaf area, root and shoot growth, and biomass [20,22,24,28,46].…”
Section: Si Accumulation In Strawberry Plantsmentioning
confidence: 97%
See 2 more Smart Citations
“…The following studies also reported that Si treatments signi cantly improved vegetative growth in strawberry plants [46,48,49] and other plants [50,51]. The differential response of the potassium silicate treatment in strawberry plants improved the 'plant's physiological traits, such as leaf area, root and shoot growth, and biomass [20,22,24,28,46].…”
Section: Si Accumulation In Strawberry Plantsmentioning
confidence: 97%
“…Similarly, different Si treatments in strawberries and other fruit crops were reported to increase the fruit yield [23,28,52]. However, most studies were conducted under controlled environmental conditions [24,47,48,52] or open elds [23]. Our study evaluated the effective concentration of Si foliar spray application for strawberry production and overall plant health under high tunnel conditions.…”
Section: Si Accumulation In Strawberry Plantsmentioning
confidence: 99%
See 1 more Smart Citation